Standards for digital cooperation - Michel Girard (Centre for International Governance Innovation (CIGI), 2020)
Global data standards are urgently needed to foster digital cooperation and manage global tech platforms. No global organization is currently mandated to coordinate the development, maintenance and use of technical standards covering data value chains and policy-oriented standards covering data governance. Precedents exist where standards development work is coordinated by international organizations in sectors of the economy operating across borders, from aviation and maritime shipping to meteorology, food production, public health and the management of the internet. This paper proposes the creation of a Data Standards Task Force (DSTF), which would be entrusted with a dual mandate: enabling the development of technical standards to create data value chains and being accountable for the development of data governance standards needed by regulators to properly frame the leading big tech platforms (Facebook, Amazon, Apple, Microsoft and Google). The ultimate objective of the DSTF would be to create the required architecture for a "single data zone" where data can circulate freely between participating jurisdictions.
Keywords: 330; Digitalization; Standardization; International Business Cooperation; Digitalisierung; Standardisierung; Internationale Unternehmenskooperation